The Dynamic of Repression: The Global Impact of the Stalinist Model, 1944-1953 (Mongolian Journal of International Affairs, 2014)
No abstract available. DOI: http://dx.doi.org/10.5564/mjia.v0i10.123 The Mongolian Journal of International Affairs; Number 10, 2003, Pages 120-155